Towards a survey of foreign language teaching and learning in secondary education in Trinidad and Tobago - Some initial comments - Rousseau, Lystra (My University, 1980)
This paper attempted to focus attention and comment on aspects of foreign language teaching and learning in Trinidad and Tobago that were cause for concern. Sources of information for the paper included: Curriculum Studies by Diploma in Education (Dip. Ed.) students, 1977-78 and 1978-1970; Social Studies by Dip. Ed. students; and remarks by students on the Dip. Ed. course, French teachers, foreign language supervisors, principals, and secondary school students.
Keywords: foreign languages; teaching and learning; secondary education